Exploring the Correlation Between Self-Esteem and Academic Success Among Special Needs Students in Kwara State, Nigeria - Famolu, Florence (Jurnal Kajian Bimbingan dan Konseling, 2025)
Special education has shifted from a position of delivering professional services to students with disabilities to a system that seeks to encompass the broad concept of promoting quality education for students. This study examined the correlation between self-esteem and academic success among special needs students in Kwara State, Nigeria. the study adopted a descriptive survey research type. special needs students in the three local government areas in Ilorin, Ilorin South, East, and West Local Governments Area constituted the total population for this research. The researcher designed questionnaire was entitled: self-esteem as correlate of academic success among special needs students’ questionnaire” (SECASNSQ). 200 questionnaire forms were administered. Research questions were answered using mean score, while inferential statistics of mean, standard deviation and Pearson Moment Correlation (PPMC) were used to test the formulated hypotheses. Statistical Package for Social Sciences (SPSS) version 23.0 and Microsoft Excel was used to analyse both inferential and descriptive statistical data. The hypotheses were tested at 0.05 significance level. The finding of the study showed that: Self-esteem (academic ability, physical ability, social ability, emotional ability, general self-worth ability and scholastic ability) influence Self-esteem as correlate of academic success of special needs students in Kwara State. More so, there was no significant relationship between Self-esteem and academic success of special needs students in Kwara state in Kwara state. There was significant relationship between religion, school type, age and Self-esteem and academic success of special needs students in Kwara State. The findings concluded that while Self-esteem may not directly influence academic success among special needs students in Kwara State, factors such as religion, school type, and age significantly impact both Self-esteem and academic success. These relationships highlight the importance of considering a range of contextual and personal factors when addressing the needs of special needs students and developing strategies to support their academic and personal development. Based on the findings of the study, it was recommended among others that school counsellors, parents and other stakeholders in the education sector should enhance adolescents’ interpersonal relationship by strengthening their physical, social and emotional Self-esteems through relevant social skills training and counseling interventions.